PENGARUH KOMITMEN ORGANISASI TERHADAP KINERJA AUDITOR DENGAN INDEPENDENSI, INTEGRITAS, DAN PEMAHAMAN GOOD GOVERNANCE SEBAGAI VARIABEL PEMODERASI (Studi Empiris pada KAP di Jawa Tengah dan DIY) - Prasetyaningrum, Nurita Elfani (Universitas Slamet Riyadi, 2020)
This study aims to (1) analyze the effect of organizational commitment on auditor performance (2) analyze independence as a moderating effect on organizational commitment on auditor performance (3) analyze integrity as a moderating effect on organizational commitment on auditor performance (4) analyze understanding of good governance as moderating the effect of organizational commitment on auditor performance. This study uses a sample of 48 auditors working on KAP in Central Java and Yogyakarta. Sampling using a purposive sampling technique. Data analysis techniques using regression analysis with absolute difference test. The findings show (1) organizational commitment has a significant effect on auditor performance (2) independence is a moderating variable that can strengthen the effect of organizational commitment on auditor performance (3) integrity is a moderating variable that can strengthen the effect of organizational commitment on auditor performance (4) understanding of good governance is a moderating variable that can strengthen the effect of organizational commitment on auditor performance.